2022
DOI: 10.3389/fenrg.2021.778757
|View full text |Cite
|
Sign up to set email alerts
|

A Race Between Economic Growth and Carbon Emissions: How Will the CO2 Emission Reach the Peak in Transportation Industry?

Abstract: Promoting carbon emissions of the transportation industry to reach the peak as soon as possible is an effective way to control carbon emissions in China. Combined with the logarithmic mean Divisia index (LMDI) model and the Tapio decoupling model, this paper tries to predict and analyze the time, path, and quality of carbon peaking in the transportation industry in China and its eastern, central, and western regions. The research shows the following: 1) Under the “benchmark scenario,” the transportation indust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…After confirming the occurrence of the long-term association by the ARDL test, we computed the parameters for the long-term associations. This result relates to the findings of [ 39 , 40 , 45 ].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…After confirming the occurrence of the long-term association by the ARDL test, we computed the parameters for the long-term associations. This result relates to the findings of [ 39 , 40 , 45 ].…”
Section: Resultssupporting
confidence: 90%
“…Torun et al [ 38 ] with the application of wavelet-based technique showed that CO 2 emissions and GDP growth have a positive interrupted short-term and strong unidirectional long-run relationship, thereby, specifying that economic growth propels environmental destruction. Wu et al [ 39 ] used the index of logarithmic mean divisia with the decoupling Tapio model to establish that CO 2 emissions peaks take into account air quality, path, and time in the transportation sector. They showed that the improved transportation sector fuelled CO 2 emissions to its peak.…”
Section: Introductionmentioning
confidence: 99%
“…Gao and Sun [16] use the grey relational analysis model to investigate the evolutionary relationship of TCE and relevant factors in Jilin Province. Wu et al [17] combine the Logarithmic Mean Divisia Index (LMDI) model with the Tapio decoupling model, predict and analyze the time, path, and quality of carbon peaking in the transportation industry in China and its eastern, central, and western regions. Byers et al [18] have studied and analyzed the lowcarbon development measures of the UK transport system from 2010 to 2050 by building a practical energy analysis framework for future transport routes.…”
Section: Research On Transportation Carbon Emission Predictionmentioning
confidence: 99%
“…where i represents the province, t represents the year, and the dependent variable CI represents the carbon emission intensity, which is the explained variable; represents the carbon emission intensity, which is the explained variable; FD represents the independent variable financial development, which is the core explanatory variable; T represents technological progress; Z is the control variable, including regional openness (Open), human capital (Hc), infrastructure level (In f r), industrial structure (Stru), and urbanization level (Urb); Vi represents the individual effect, Vt represents the time effect,ε represents the random error term, and a 0 is the constant term of Model (3). The square term of financial development (FD 2 ) is added to the model to verify whether there is an inverted U-shaped relationship between financial development and carbon emissions.…”
Section: Empirical Modelmentioning
confidence: 99%
“…The Environmental Performance Index (EPI) assessment results released by global authorities in 2020 showed that China's EPI ranking remained low across the globe. Meanwhile, as extreme weather conditions increase, it is important to improve energy utilization, accelerate technological progress, reduce carbon emissions, and reach the carbon peak as soon as possible [2][3][4]. In China's Standards Plan, economic development, sci-tech progress, and ecological conservation are given equal importance.…”
Section: Introductionmentioning
confidence: 99%